Impact of a passive upper-body exoskeleton on muscular activity and precision in overhead single and dual tasks: an explorative randomized crossover study - Gräf, Julia; Grospretre, Sidney; Argubi-Wollesen, Andreas; Wollesen, Bettina (Frontiers in Neurology, 2024)
Introduction Tasks performed at or above head height in industrial workplaces pose a significant challenge due to their association with musculoskeletal disorders. Upper-body exoskeletons have been identified as a potential solution for mitigating musculoskeletal loads and fighting against excessive muscular fatigue. However, the influence of such support on fine motor control, as well as on cognitive-motor interference, has received limited attention thus far. Therefore, this crossover randomized study aimed to investigate the impact of the use of a passive upper-body exoskeleton in the presence of muscular fatigue or not. Additionally, focusing on differences between single (ST) and dual (DT) industrial tasks consisting of overhead speed and accuracy exercises. Methods In both scenarios, N = 10 participants (5 male/5 female) engaged in an overhead precision task using a nail gun to precisely target specific areas on three differently sized regions, based on Fitts’ law paradigm (speed-accuracy trade-off task). This was done with and without the passive upper-body exoskeleton, before and immediately after a fatiguing exercise of shoulder and leg muscles. In addition, a second task (dual-task, DT) was carried out in which the occurrence of an auditory signal had to be counted. The main outcomes were muscular activation of the shoulder girdle as well as the time to perform speed-accuracy tasks of different difficulty indexes (calculated by means of Fitts’ law). Results and discussion In the absence of fatigue, the exoskeleton did not affect the speed-accuracy trade-off management of participants in the single task, but it did in the dual-task conditions. However, after muscle fatigue, the speed-accuracy trade-off was differently affected when comparing its execution with or without the exoskeleton. In general, the dual task resulted in longer times to perform the different tasks, whether it was with or without the exoskeleton. Furthermore, the use of the exoskeleton decreased muscle activity, which is associated with less physical effort, but only significantly for the M. deltoideus and M. trapezius when compared by tasks. Overall, these study findings highlight the potential supportive effects of using an upper-body exoskeleton for industrial overhead tasks.